A flower is born: an update on Arabidopsis floral meristem formation. (February 2017) - Denay, Grégoire; Chahtane, Hicham; Tichtinsky, Gabrielle; Parcy, François
Highlights: Flower development requires de novo formation of a stem cell niche. Auxin and cytokinin signaling interact to trigger emergence of floral meristems. Meristem growth and floral fate determination are intimately coupled. Several key floral regulators share unexpected structural features. Abstract : In Arabidopsis, floral meristems appear on the flanks of the inflorescence meristem. Their stereotypic development, ultimately producing the four whorls of floral organs, is essentially controlled by a network coordinating growth and cell-fate determination. This network integrates hormonal signals, transcriptional regulators, and mechanical constraints. Mechanisms regulating floral meristem formation have been studied at many different scales, from protein structure to tissue modeling. In this paper, we review recent findings related to the emergence of the floral meristem and floral fate determination and examine how this field has been impacted by recent technological developments.